Archives Information Systems and the Needs of Organizational Actors - Maurel, Dominique (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This communication presents the conceptual framework of a study on how records/archives information systems answer the needs of organizational actors. Factors under consideration cover the organization’s information environment, the cognitive, affective and contextual components of information behaviours, information processing methods, and features of the system-users interface. Cette communication présente le cadre conceptuel d’une étude sur l’adéquation des systèmes d’information archivistiques aux besoins des acteurs organisationnels. Les facteurs considérés portent sur l’environnement informationnel de l’organisation, les composantes cognitives, affectives et contextuelles des comportements informationnels, les processus de traitement de l’information, et les composantes de l’interface système-utilisateurs.